The young ninja Dia yang tak tersentuh maut Simon Higgins ; penerjemah, Aan ; penyunting, Perwira Leo S. ; ilustrasi, Wisnu. - HIGGINS, Simon; Aan ; Leo S, perwira (B First, 2010)
ix , 316 hlm. : ilus. ; 21 cm. (2 eks)